Learning Science in Informal Environments: People, Places, and Pursuits - National Research Council (The National Academies Press, 2009)
Informal science is a burgeoning field that operates across a broad range of venues and envisages learning outcomes for individuals, schools, families, and society. The evidence base that describes informal science, its promise, and effects is informed by a range of disciplines and perspectives, including field-based research, visitor studies, and psychological and anthropological studies of learning. Learning Science in Informal Environments draws together disparate literatures, synthesizes the state of knowledge, and articulates a common framework for the next generation of research on learning science in informal environments across a life span. Contributors include recognized experts in a range of disciplines2014research and evaluation, exhibit designers, program developers, and educators. They also have experience in a range of settings2014museums, after-school programs, science and technology centers, media enterprises, aquariums, zoos, state parks, and botanical gardens. Learning Science in Informal Environments is an invaluable guide for program and exhibit designers, evaluators, staff of science-rich informal learning institutions and community-based organizations, scientists interested in educational outreach, federal science agency education staff, and K-12 science educators.

Effective Chemistry Communication in Informal Environments - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Chemistry plays a critical role in daily life, impacting areas such as medicine and health, consumer products, energy production, the ecosystem, and many other areas. Communicating about chemistry in informal environments has the potential to raise public interest and understanding of chemistry around the world. However, the chemistry community lacks a cohesive, evidence-based guide for designing effective communication activities. This report is organized into two sections. Part A: The Evidence Base for Enhanced Communication summarizes evidence from communications, informal learning, and chemistry education on effective practices to communicate with and engage publics outside of the classroom; presents a framework for the design of chemistry communication activities; and identifies key areas for future research. Part B: Communicating Chemistry: A Framework for Sharing Science is a practical guide intended for any chemists to use in the design, implementation, and evaluation of their public communication efforts.

Evaluating Hearing Loss for Individuals with Cochlear Implants - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The U.S. Social Security Administration (SSA) administers programs that provide disability benefits. Once SSA establishes the presence of a severe impairment, it determines whether the impairment meets the criteria in the Listing of Impairments (Listings) that qualify a candidate for disability benefits. The current Listings that address hearing loss treated with cochlear implantation contain criteria that evaluate hearing ability through a speech recognition test called the Hearing in Noise Test (HINT). Since its development in 1994, the HINT has been widely used to measure cochlear implant candidacy and postoperative outcomes. However, the test characteristics, the state of cochlear implant technology, and the environment that made the HINT a common choice of assessment in 1994 are different in 2021. The HINT has several limitations in its characteristics and deviation from its intended use. At the request of SSA, the National Academies of Sciences, Engineering, and Medicine convened a consensus study committee to identify and recommend generalized testing procedures and criteria for evaluating the level of functional hearing ability needed to make a disability determination in adults and children after cochlear implantation. The committee's report, Evaluating Hearing Loss for Individuals with Cochlear Implants, details and supports its findings, conclusions, and recommendations based on published evidence and professional judgment.

Leading Health Indicators 2030: Advancing Health, Equity, and Well-Being - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Beginning in 1979 and in each subsequent decades, the U.S. Department of Health and Human Services (HHS) has overseen the Healthy People initiative to set national goals and objectives for health promotion and disease prevention. At the request of HHS, this study presents a slate of Leading Health Indicators (LHIs) that will serve as options for the Healthy People Federal Interagency Workgroup to consider as they develop the final criteria and set of LHIs for Healthy People 2030.

Learning Science Through Computer Games and Simulations - National Research Council (The National Academies Press, 2011)
At a time when scientific and technological competence is vital to the nation's future, the weak performance of U.S. students in science reflects the uneven quality of current science education. Although young children come to school with innate curiosity and intuitive ideas about the world around them, science classes rarely tap this potential. Many experts have called for a new approach to science education, based on recent and ongoing research on teaching and learning. In this approach, simulations and games could play a significant role by addressing many goals and mechanisms for learning science: the motivation to learn science, conceptual understanding, science process skills, understanding of the nature of science, scientific discourse and argumentation, and identification with science and science learning. To explore this potential, Learning Science: Computer Games, Simulations, and Education, reviews the available research on learning science through interaction with digital simulations and games. It considers the potential of digital games and simulations to contribute to learning science in schools, in informal out-of-school settings, and everyday life. The book also identifies the areas in which more research and research-based development is needed to fully capitalize on this potential. Learning Science will guide academic researchers; developers, publishers, and entrepreneurs from the digital simulation and gaming community; and education practitioners and policy makers toward the formation of research and development partnerships that will facilitate rich intellectual collaboration. Industry, government agencies and foundations will play a significant role through start-up and ongoing support to ensure that digital games and simulations will not only excite and entertain, but also motivate and educate.

Learning to Think Spatially - National Research Council (The National Academies Press, 2006)
Learning to Think Spatially examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K201312 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K201312 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.

Learning Through Citizen Science: Enhancing Opportunities by Design - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
In the last twenty years, citizen science has blossomed as a way to engage a broad range of individuals in doing science. Citizen science projects focus on, but are not limited to, nonscientists participating in the processes of scientific research, with the intended goal of advancing and using scientific knowledge. A rich range of projects extend this focus in myriad directions, and the boundaries of citizen science as a field are not clearly delineated. Citizen science involves a growing community of professional practitioners, participants, and stakeholders, and a thriving collection of projects. While citizen science is often recognized for its potential to engage the public in science, it is also uniquely positioned to support and extend participants' learning in science. Contemporary understandings of science learning continue to advance. Indeed, modern theories of learning recognize that science learning is complex and multifaceted. Learning is affected by factors that are individual, social, cultural, and institutional, and learning occurs in virtually any context and at every age. Current understandings of science learning also suggest that science learning extends well beyond content knowledge in a domain to include understanding of the nature and methods of science. Learning Through Citizen Science: Enhancing Opportunities by Design discusses the potential of citizen science to support science learning and identifies promising practices and programs that exemplify the promising practices. This report also lays out a research agenda that can fill gaps in the current understanding of how citizen science can support science learning and enhance science education.

Science Teachers' Learning: Enhancing Opportunities, Creating Supportive Contexts - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
Currently, many states are adopting the Next Generation Science Standards (NGSS) or are revising their own state standards in ways that reflect the NGSS. For students and schools, the implementation of any science standards rests with teachers. For those teachers, an evolving understanding about how best to teach science represents a significant transition in the way science is currently taught in most classrooms and it will require most science teachers to change how they teach. That change will require learning opportunities for teachers that reinforce and expand their knowledge of the major ideas and concepts in science, their familiarity with a range of instructional strategies, and the skills to implement those strategies in the classroom. Providing these kinds of learning opportunities in turn will require profound changes to current approaches to supporting teachers' learning across their careers, from their initial training to continuing professional development. A teacher's capability to improve students' scientific understanding is heavily influenced by the school and district in which they work, the community in which the school is located, and the larger professional communities to which they belong. Science Teachers' Learning provides guidance for schools and districts on how best to support teachers' learning and how to implement successful programs for professional development. This report makes actionable recommendations for science teachers' learning that take a broad view of what is known about science education, how and when teachers learn, and education policies that directly and indirectly shape what teachers are able to learn and teach. The challenge of developing the expertise teachers need to implement the NGSS presents an opportunity to rethink professional learning for science teachers. Science Teachers' Learning will be a valuable resource for classrooms, departments, schools, districts, and professional organizations as they move to new ways to teach science.

Promoting the Educational Success of Children and Youth Learning English: Promising Futures - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Educating dual language learners (DLLs) and English learners (ELs) effectively is a national challenge with consequences both for individuals and for American society. Despite their linguistic, cognitive, and social potential, many ELs2014who account for more than 9 percent of enrollment in grades K-12 in U.S. schools2014are struggling to meet the requirements for academic success, and their prospects for success in postsecondary education and in the workforce are jeopardized as a result. Promoting the Educational Success of Children and Youth Learning English: Promising Futures examines how evidence based on research relevant to the development of DLLs\/ELs from birth to age 21 can inform education and health policies and related practices that can result in better educational outcomes. This report makes recommendations for policy, practice, and research and data collection focused on addressing the challenges in caring for and educating DLLs\/ELs from birth to grade 12.

Improving Adult Literacy Instruction: Supporting Learning and Motivation - National Research Council
Virtually everyone needs a high level of literacy in both print and digital media to negotiate most aspects of 21st century life-succeeding in a competitive job market, supporting a family, navigating health information, and participating in civic activities. Yet, according to a recent survey estimate, more than 90 million adults in the United States lack the literacy skills needed for fully productive and secure lives. At the request of the U.S. Department of Education, the National Research Council convened a committee of experts from many disciplines to synthesize research on literacy and learning in order to improve instruction for those served in adult education in the U.S. The committee's report, Improving Adult Literacy Instruction: Options for Practice and Research, recommends a program of research and innovation to gain a better understanding of adult literacy learners, improve instruction, and create the supports adults need for learning and achievement. Improving Adult Literacy Instruction: Supporting Learning and Motivation, which is based on the report, describes principles of effective instruction to guide those who design and administer adult literacy programs and courses. It also explores ways to motivate learners to persist in their studies, which is crucial given the thousands of hours of study and practice required to become proficient.The booklet concludes with a look at technologies that show promise for supporting individual learners and freeing busy adults from having to be in a particular place in order to practice their literacy skills. Although this booklet is not intended as a \

Discipline-Based Education Research: Understanding and Improving Learning in Undergraduate Science and Engineering - National Research Council (The National Academies Press, 2012)
The National Science Foundation funded a synthesis study on the status, contributions, and future direction of discipline-based education research (DBER) in physics, biological sciences, geosciences, and chemistry. DBER combines knowledge of teaching and learning with deep knowledge of discipline-specific science content. It describes the discipline-specific difficulties learners face and the specialized intellectual and instructional resources that can facilitate student understanding. Discipline-Based Education Research is based on a 30-month study built on two workshops held in 2008 to explore evidence on promising practices in undergraduate science, technology, engineering, and mathematics (STEM) education. This book asks questions that are essential to advancing DBER and broadening its impact on undergraduate science teaching and learning. The book provides empirical research on undergraduate teaching and learning in the sciences, explores the extent to which this research currently influences undergraduate instruction, and identifies the intellectual and material resources required to further develop DBER. Discipline-Based Education Research provides guidance for future DBER research. In addition, the findings and recommendations of this report may invite, if not assist, post-secondary institutions to increase interest and research activity in DBER and improve its quality and usefulness across all natural science disciples, as well as guide instruction and assessment across natural science courses to improve student learning. The book brings greater focus to issues of student attrition in the natural sciences that are related to the quality of instruction. Discipline-Based Education Research will be of interest to educators, policy makers, researchers, scholars, decision makers in universities, government agencies, curriculum developers, research sponsors, and education advocacy groups.

Learning and Instruction: A SERP Research Agenda - National Research Council (The National Academies Press, 2004)
The Strategic Education Research Partnership (SERP) is a bold, ambitious plan that proposes a revolutionary program of education research and development. Its purpose is to construct a powerful knowledge base, derived from both research and practice, that will support the efforts of teachers, school administrators, colleges of education, and policy officials2014with the ultimate goal of significantly improving student learning. The proposals in this book have the potential to substantially improve the knowledge base that supports teaching and learning by pursuing answers to questions at the core of teaching practices. It calls for the linking of research and development, including instructional programs, assessment tools, teacher education programs, and materials. Best of all, the book provides a solid framework for a program of research and development that will be genuinely useful to classroom teachers.

Measuring Access to Learning Opportunities - National Research Council (The National Academies Press, 2003)
Since 1968 the Elementary and Secondary School Civil Rights Compliance Report (known as the E&S survey) has been used to gather information about possible disparities in access to learning opportunities and violations of students2019 civil rights. Thirty-five years after the initiation of the E&S survey, large disparities remain both in educational outcomes and in access to learning opportunities and resources. These disparities may reflect violations of students2019 civil rights, the failure of education policies and practices to provide students from all backgrounds with a similar educational experience, or both. They may also reflect the failure of schools to fully compensate for disparities and current differences in parents2019 education, income, and family structure. The Committee on Improving Measures of Access to Equal Educational Opportunities concludes that the E&S survey continues to play an essential role in documenting these disparities and in providing information that is useful both in guiding efforts to protect students2019 civil rights and for informing educational policy and practice. The committee also concludes that the survey2019s usefulness and access to the survey data could be improved.

Best Care at Lower Cost: The Path to Continuously Learning Health Care in America - Institute of Medicine (The National Academies Press, 2013)
America's health care system has become too complex and costly to continue business as usual. Best Care at Lower Cost explains that inefficiencies, an overwhelming amount of data, and other economic and quality barriers hinder progress in improving health and threaten the nation's economic stability and global competitiveness. According to this report, the knowledge and tools exist to put the health system on the right course to achieve continuous improvement and better quality care at a lower cost. The costs of the system's current inefficiency underscore the urgent need for a systemwide transformation. About 30 percent of health spending in 20092014roughly 750 billion2014was wasted on unnecessary services, excessive administrative costs, fraud, and other problems. Moreover, inefficiencies cause needless suffering. By one estimate, roughly 75,000 deaths might have been averted in 2005 if every state had delivered care at the quality level of the best performing state. This report states that the way health care providers currently train, practice, and learn new information cannot keep pace with the flood of research discoveries and technological advances. About 75 million Americans have more than one chronic condition, requiring coordination among multiple specialists and therapies, which can increase the potential for miscommunication, misdiagnosis, potentially conflicting interventions, and dangerous drug interactions. Best Care at Lower Cost emphasizes that a better use of data is a critical element of a continuously improving health system, such as mobile technologies and electronic health records that offer significant potential to capture and share health data better. In order for this to occur, the National Coordinator for Health Information Technology, IT developers, and standard-setting organizations should ensure that these systems are robust and interoperable. Clinicians and care organizations should fully adopt these technologies, and patients should be encouraged to use tools, such as personal health information portals, to actively engage in their care. This book is a call to action that will guide health care providers; administrators; caregivers; policy makers; health professionals; federal, state, and local government agencies; private and public health organizations; and educational institutions.

Green Schools: Attributes for Health and Learning - National Research Council (The National Academies Press, 2007)
Evidence has accumulated that shows that the quality of indoor environments can affect the health and productivity of adults and children. One consequence is that a movement has emerged to promote the design of schools that have fewer adverse environmental effects. To examine the potential of such design for improving education, several private organizations asked the NRC to review and assess the health and productivity benefits of green schools. This report provides an analysis of the complexity of making such a determination; and an assessment of the potential human health and performance benefits of improvements in the building envelope, indoor air quality, lighting, and acoustical quality. The report also presents an assessment of the overall building condition and student achievement, and offers an analysis of and recommendations for planning and maintaining green schools including research considerations.

Mathematics Learning in Early Childhood: Paths Toward Excellence and Equity - National Research Council (The National Academies Press, 2009)
Early childhood mathematics is vitally important for young children's present and future educational success. Research demonstrates that virtually all young children have the capability to learn and become competent in mathematics. Furthermore, young children enjoy their early informal experiences with mathematics. Unfortunately, many children's potential in mathematics is not fully realized, especially those children who are economically disadvantaged. This is due, in part, to a lack of opportunities to learn mathematics in early childhood settings or through everyday experiences in the home and in their communities. Improvements in early childhood mathematics education can provide young children with the foundation for school success. Relying on a comprehensive review of the research, Mathematics Learning in Early Childhood lays out the critical areas that should be the focus of young children's early mathematics education, explores the extent to which they are currently being incorporated in early childhood settings, and identifies the changes needed to improve the quality of mathematics experiences for young children. This book serves as a call to action to improve the state of early childhood mathematics. It will be especially useful for policy makers and practitioners-those who work directly with children and their families in shaping the policies that affect the education of young children.

The Internet Under Crisis Conditions: Learning from September 11 - National Research Council (The National Academies Press, 2003)
This report presents findings of a workshop featuring representatives of Internet Service Providers and others with access to data and insights about how the Internet performed on and immediately after the September 11 attacks. People who design and operate networks were asked to share data and their own preliminary analyses among participants in a closed workshop. They and networking researchers evaluated these inputs to synthesize lessons learned and derive suggestions for improvements in technology, procedures, and, as appropriate, policy.

Hearing Health Care for Adults: Priorities for Improving Access and Affordability - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The loss of hearing - be it gradual or acute, mild or severe, present since birth or acquired in older age - can have significant effects on one's communication abilities, quality of life, social participation, and health. Despite this, many people with hearing loss do not seek or receive hearing health care. The reasons are numerous, complex, and often interconnected. For some, hearing health care is not affordable. For others, the appropriate services are difficult to access, or individuals do not know how or where to access them. Others may not want to deal with the stigma that they and society may associate with needing hearing health care and obtaining that care. Still others do not recognize they need hearing health care, as hearing loss is an invisible health condition that often worsens gradually over time. In the United States, an estimated 30 million individuals (12.7 percent of Americans ages 12 years or older) have hearing loss. Globally, hearing loss has been identified as the fifth leading cause of years lived with disability. Successful hearing health care enables individuals with hearing loss to have the freedom to communicate in their environments in ways that are culturally appropriate and that preserve their dignity and function. Hearing Health Care for Adults focuses on improving the accessibility and affordability of hearing health care for adults of all ages. This study examines the hearing health care system, with a focus on non-surgical technologies and services, and offers recommendations for improving access to, the affordability of, and the quality of hearing health care for adults of all ages.

Emergency Alert and Warning Systems: Current Knowledge and Future Research Directions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Following a series of natural disasters, including Hurricane Katrina, that revealed shortcomings in the nation's ability to effectively alert populations at risk, Congress passed the Warning, Alert, and Response Network (WARN) Act in 2006. Today, new technologies such as smart phones and social media platforms offer new ways to communicate with the public, and the information ecosystem is much broader, including additional official channels, such as government social media accounts, opt-in short message service (SMS)-based alerting systems, and reverse 911 systems; less official channels, such as main stream media outlets and weather applications on connected devices; and unofficial channels, such as first person reports via social media. Traditional media have also taken advantage of these new tools, including their own mobile applications to extend their reach of beyond broadcast radio, television, and cable. Furthermore, private companies have begun to take advantage of the large amounts of data about users they possess to detect events and provide alerts and warnings and other hazard-related information to their users. More than 60 years of research on the public response to alerts and warnings has yielded many insights about how people respond to information that they are at risk and the circumstances under which they are most likely to take appropriate protective action. Some, but not all, of these results have been used to inform the design and operation of alert and warning systems, and new insights continue to emerge. Emergency Alert and Warning Systems reviews the results of past research, considers new possibilities for realizing more effective alert and warning systems, explores how a more effective national alert and warning system might be created and some of the gaps in our present knowledge, and sets forth a research agenda to advance the nation's alert and warning capabilities.

Toward Quality Measures for Population Health and the Leading Health Indicators - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Committee on Quality Measures for the Healthy People Leading Health Indicators was charged by the Office of the Assistant Secretary for Health to identify measures of quality for the 12 Leading Health Indicator (LHI) topics and 26 Leading Health Indicators in Healthy People 2020 (HP2020), the current version of the Department of Health and Human Services (HHS) 10-year agenda for improving the nation's health. The scope of work for this project is to use the nine aims for improvement of quality in public health (population-centered, equitable, proactive, health promoting, risk reducing, vigilant, transparent, effective, and efficient) as a framework to identify quality measures for the Healthy People Leading Health Indicators (LHIs). The committee reviewed existing literature on the 12 LHI topics and the 26 Leading Health Indicators. Quality measures for the LHIs that are aligned with the nine aims for improvement of quality in public health will be identified. When appropriate, alignments with the six Priority Areas for Improvement of Quality in Public Health will be noted in the Committee's report. Toward Quality Measures for Population Health and the Leading Health Indicators also address data reporting and analytical capacities that must be available to capture the measures and for demonstrating the value of the measures to improving population health. Toward Quality Measures for Population Health and the Leading Health Indicators provides recommendations for how the measures can be used across sectors of the public health and health care systems. The six priority areas (also known as drivers) are population health metrics and information technology; evidence-based practices, research, and evaluation; systems thinking; sustainability and stewardship; policy; and workforce and education.